2022
DOI: 10.33487/edumaspul.v6i2.4099
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooperative Learning Model Type of Team Assisted Indivisualization Assisted LKPD on Mathematics Learning Outcomes

Abstract: The purpose of the study was to determine the students' mathematics learning outcomes by using a cooperative learning model of team assisted individualization type assisted by hots-based worksheets; and the effect of cooperative learning model type team assisted individualization assisted LKPD based hots on students' mathematics learning outcomes. The method used is an experiment with sampling determined by taking the available classes without doing random sampling. The experimental class and control class wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The results of the test of significant difference uphold the previous studies on the positive effects of TAI in mathematics performance of the students (i.e. Al Arsat et al, 2022;Tinungki et al, 2022;Tinungki, 2017;Sari et al, 2022).…”
Section: Findings and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the test of significant difference uphold the previous studies on the positive effects of TAI in mathematics performance of the students (i.e. Al Arsat et al, 2022;Tinungki et al, 2022;Tinungki, 2017;Sari et al, 2022).…”
Section: Findings and Discussionsupporting
confidence: 85%
“…Majority of the studies that applied TAI in mathematics classroom showed improved student performance (i.e. Al Arsat et al, 2022;Tinungki et al, 2022;Tinungki, 2017;Sari et al, 2022). However, there is very limited…”
Section: Introductionmentioning
confidence: 99%